An Examination of School Counselors' Career-Sustaining Behaviors and Their Relationship to Burnout and Job Satisfaction. Issue 1 (2nd January 2023) - Mullen, Patrick R.; Niles, Jennifer; Hinchey, Kaitlin J.; Leger, Ryan; Dorais, Stephanie
ABSTRACT: In this study, we collected surveys from 750 school counselors to gather information about the importance of the key career-sustaining behaviors to better understand school counselors' preferred self-care strategies. Using a factor analytic approach, we also examined the Career-Sustaining Behaviors Questionnaire's (CSBQ) internal structure to see how the career-sustaining behaviors to group together. Finally, we compared scores on the CSBQ to participants' job satisfaction and burnout. The findings provide insight into the CSBQ dimensions and how school counselors' preferences for particular self-care strategies relate to their well-being. We describe implications for future research that build upon the current study.